The problem of reception in the poetic modernity debate (Journal of the College of Basic Education, 2023)
There is no difference of opinion that poetry in our present time has reached a point where it is no longer attracting any attention.A little bit, which makes us wonder about the true importance of poetry compared to its realistic marginality.No one can claim today that poetry still retains the importance it once had.And that he does not suffer from a crisis, one of the reasons for which may be that the poets wanted to write poetry worthy ofAt the time of scientific developments and the technological revolution, although these developments may threaten its survival, but they are inAt the same time, it gives him new tasks that other arts may not be able to fulfill because of his linguistic nature.The one who can express what no one else can express.